Smart Sustainable Cities Profile: Tbilisi, Georgia - United Nations Economic Commission for Europe (United Nations, 2023)
The Smart Sustainability Profile of Tbilisi presents the outcome of the evaluation of the city against the Key Performance Indicators for Smart Sustainable Cities. It proposes actions for the city to make progress toward achieving the SDGs. The City Profile will guide Grodno in developing, reviewing and implementing urban policies, programmes, and projects, and in building partnerships with other stakeholders with a view to reinforcing the implementation of the 2030 Agenda for Sustainable Development and SDG11 at the city level.